THE EFFECT OF BAIT ON CATCH OF TROLLING LINE IN TANJUNG MUTIARA DISTRICT AGAM REGENCY WEST SUMATERA PROVINCE - Kurniawan, Muhammad; Rengi, Pareng; ', Usman (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Skipjack tuna (Katsuwonus pelamis) and others tuna (Thunnus), in western Sumatra is one of fisheries resources that has important economic value. Skipjack and others tuna heversted by trolling line. This study used experimental method with design of 3x3 factorial pattern. The catch During the study consisting of 2 trips with 10 days catching time, with the operation time of fishing gear for 1998 minutes, got the catch as many as 575 fish, with the average catch of fish is 0.29 tail / minute. Based on the result of data analysis, there is no interaction between the bait and the color bait to the catch trolling line in Tanjung Mutiara district Agam Regency West Sumatera Province.Keywords: Trolling line, Catch, Bait, Tanjung Mutiara district